Production Methy Ester Sulfonate (MES) Based Rubber Seeds As One Of Chemical Injection Solutions In Enhanched Oil Recovery (EOR) Process - Ineke Febrina Anggraini; Muhammad Said; Muhammad Faizal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
One attempt to increase the recovery of oil from a reservoir is by injecting the surfactant. Surfactant is used for lowered tension interfaces (interfacial tension) between oil and water so able bring oil exit pores reservoir. It is a good opportunity for develop type surfactant based oil vegetable that is from oil seed rubber. As known from the chemical composition in oil seed rubber contain olein amounted to 39.45 % wt, which is almost approaching value olein from petrochemicals based by 40.7 %. For produce suitable surfactants with characteristics required by oil industry, then do formulation with combine MES surfactant produced with ingredients additives other as appropriate to produce a capable formula for give best performance to be applied on oil industry. From the test result, the MES from the rubber seed oil obtained has fulfilled the surfactant requirement with the value from soaking % crude oil recovery value is 0,815 % - 3,91 % with the best value is 3,91 %, pH value is 7,2 -8,2, density value is 1,006 - 1,065, the compability test result, both catalyst can be used because there is no difference and show positive results that there is no precipitate and clear colored of MES surfactant and also for Interfacial Tension test result is 0.373 - 0.254 dyne/cm.